Internet of things : energy, industry, and healthcare - Rana, Arun Kumar (Abingdon, Oxon ; Boca Raton, FL : CRC Press, 2022)
"This book provides future research directions in energy, industry, and healthcare domain, and explores the different applications of IoT and its associated technologies. The book discusses software architecture, middleware, data processing and management as well as security, sensors and algorithms"--
OCLC-licensed vendor bibliographic record.
Keywords: Internet of things; COMPUTERS / Computer Architecture; COMPUTERS / Networking / General; COMPUTERS / Computer Engineering